Solutions manual for Financial economics - Eichberger, Jürgen (Oxford University Press, 2023)
This manual provides worked solutions to all the exercises in Financial Economics, organised according to the chapters in the original textbook.
Previously issued in print: 2002. - Includes bibliographical references (p. 173) and index. - Derived record based on print version record and publisher information